2021
DOI: 10.1016/j.cmi.2020.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal infection in HIV-infected patients with CD4+ T-cell counts under 100/μL diagnosed in a high-income country: a multicentre cohort study

Abstract: Background: Nephrotoxicity and neurotoxicity are commonly associated with polymyxin treatment; however, the emergence of multidrug-resistant Gram-negative bacteria with limited therapeutic options has resulted in increased use of polymyxins. Objectives: To determine the rates of nephrotoxicity and neurotoxicity during polymyxin treatment and whether any factors influence these. Data sources: Medline, Embase and Cochrane Library databases were searched on 2 January 2020. Study eligibility criteria: Studies repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 137 publications
0
2
0
Order By: Relevance
“…Cryptococcus can also appear in association with idiopathic CD4 + T-cell cytopenia without HIV infection, and the chance of disseminated cryptococcosis is high in patients with a CD4 + Tcell count lower than 400 cells/ml (13). Recent studies have suggested that routine screening of HIV-infected patients with a CD4 + T-cell count <100 cells/ml for cryptococcal infection can prevent CM in both resource-limited and high-income countries (14).…”
Section: Cd4 + T Cellsmentioning
confidence: 99%
“…Cryptococcus can also appear in association with idiopathic CD4 + T-cell cytopenia without HIV infection, and the chance of disseminated cryptococcosis is high in patients with a CD4 + Tcell count lower than 400 cells/ml (13). Recent studies have suggested that routine screening of HIV-infected patients with a CD4 + T-cell count <100 cells/ml for cryptococcal infection can prevent CM in both resource-limited and high-income countries (14).…”
Section: Cd4 + T Cellsmentioning
confidence: 99%
“…Evidence suggests that host immune responses to cryptococcosis play a critical role in disease progression ( 95 97 ). CM can occur following primary lung infection or by reactivation and dissemination of latent pulmonary infection in the setting of cell-mediated immunodeficiency when CD4 + T-cell counts are <100 cells/μl in the late-stages of HIV-infection ( 98 ). Previous studies have shown that CD4 + T cells possibly mediate protective host immunity against cryptococcal via production of Th1-type cytokine responses, including IL-2, IL-12, tumor necrosis factor alpha (TNF-α), and IFN-γ, which play an essential role in recruitment of lymphocytes and phagocytes to clear the infection ( 99 , 100 ).…”
Section: Common Fungal Diseases In Hiv Infectionmentioning
confidence: 99%